The Next Decade of Earth Science Research In Canadian Universities: Proceedings of the Earth Science Workshop, 1981 - Fyfe, W.; Rust, B. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1981)
Summary A workshop on university earth scienceresearch was held in Ottawa, January1981. The meeting, partly sponsored byNSERC was attended by about 100 earthscientists. Perhaps the most impressive result ofthe workshop was the spirit of coopera-tion of the participants and the expres-sion of concerns that if we are to improveour science on the national and interna-tional scenes, then we must coordinateefforts as far as possible and as rapidlyas possible. There is a great need forincreased funding levels in the sciencebut a widely held view was that this maybe achieved best by establishing somelarge projects (mega-projects) which willintegrate efforts from a large spectrum ofmembers of our community and whichwill lead to "state of the art" conclusionson problems of vital concern to ourscience and to national objectives inmineral resources. Examples of the typesof projects considered were three dimen-sional studies of the crust (lithoprobe),sedimentary basins and continentalmargins. It was recognized that universities can-not do the job alone but there should bea coordinated effort from government,industry and the universities. But univer-sities have a unique role to play in that a large population of intelligent youngpeople are available to work on newthrusts and be trained in exciting science.Universities also have wide ranging facili-ties which can be turned to such mega-projects. The general feeling of the par-ticipants was that project selection andfund raising should be coordinatedthrough the Geoscience Council of Can-ada with each group doing those parts ofthe projects for which they were uniquelysuited. Other important conclusions of theworkshop were that there is need forincreased effort in mineral resources,research in the North and environmentalstudies. Concern was expressed over thesmall number of the new senior researchfellowships being awarded In ourscience. It was also agreed that Canadashould and must take part In interna-tional research in drilling In the oceanmargins and that there is urgent need toreview the status of present and futureresearch involving Canadian ships formarine research. Finally Fyfe notes the large degree ofagreement on areas of concern whichresulted from the St. Jovite meeting ofEMR and the report of the CanadianCommittee for the Dynamics and Evolu-tion of the Lithosphère which appear inthis volume.